Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Dimensional crossover and local strain induced deflection of the spin spiral state in multiferroic NiI2 - Tianxing Jiang; Lianchuang Li; Haiyan Zhu; Hongyu Wang; Junchao Tian; Wenzhao Wang; Weiyi Pan; Haitao Wang; Changlin Zheng; Hongjun Xiang; Changsong Xu; Donglai Feng; et al. (Science Bulletin, 2026)

Wave-induced internal pumping as a sediment sorting mechanism and its implications for deltaic stratigraphic evolution: Insights from the Yellow River Delta - Shuyu Zhang; Jiewen Zheng; Pan Ji; Hongjun Zhang; Xiuhai Wang; Yonggang Jia; Xiaolei Liu (Sedimentary Geology, 2026)

The startup characteristics of a one-stage PNA process under the Fe-free influent condition with iron-containing sludge as inoculum - Yan Guo; Qianqian Li; Hongjun Zhao; Hongzhi Ma; Xiaomin Liu; Jianguo Liu; Tianlong Zheng; Qunhui Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

Boron nitride nanosheets via arginine-assisted embedded with phosphomolybdic acid as pesticide carriers for visualization in pest control - Li Hao; Minyan Zhou; Jialin Zeng; Jiechun Lin; Lan Hua; Ziting Yin; Mei Guan; Qiangcheng Zheng; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2026)

Latitude-dependent diversity and assembly processes of coastal microbial communities across multiple trophic levels in the China Seas - Yunlei Zhang; Xin Gao; Zhizhuo Shao; Yi Sun; Zheng Zhang; Hongjun Li; Jinqing Ye (Frontiers in Marine Science, 2025)
Coastal sediment ecosystems function as dynamic interfaces for land-sea interactions, harboring highly complex microbial communities which support vital ecological functions. However, the mechanisms governing microbial diversity maintenance and cross-trophic community assembly at large spatial scales remain poorly explored. In this study, a high-throughput sequencing approach was employed to analyze the bacterial, fungal and protistan communities in surface sediments of the China Seas. As indicated by higher values across most indices, bacterial communities generally exhibited greater richness and alpha diversity compared to fungal and protistan communities. Beta diversity decomposition revealed that species turnover dominated community variations across all three trophic levels, with the highest contribution in bacteria. The neutral community model revealed that stochastic processes exerted a stronger influence on bacterial assembly relative to fungi and protists. Moreover, null model analyses demonstrated that bacterial communities were primarily structured by dispersal limitation, fungal communities by ecological drift, while protistan communities co-regulated by homogeneous selection and homogenizing dispersal. Furthermore, similar latitude-dependent patterns in the α- and β- diversity were observed in bacteria and protists, yet such patterns were distinct for fungi. Finally, based on the correlations between community variations with their assembly mechanisms, regional species pools exerted the strongest influence on bacterial β-diversity, whereas local assembly processes dominated fungal β-diversity. The present study elucidates the trophic-level-dependent assembly rules of coastal microbiomes, thereby establishing a mechanistic foundation for predicting ecosystem responses to global change and informing evidence-based conservation of coastal ecosystems.

Dynamic Compaction Resistance Model Considering Stone Block Shape Effects - Xiong Bobo; Li Hongjun; Tian Bin; Chen Bofu; Zheng Qian; Li Chen; Zhang Jingkang (Geotechnical and Geological Engineering, 2025)

Deep Learning in Slope Stability Analysis: Evolution, Challenges, and Future Directions - Dejian Li; Zheng Wang; Hongjun Guo; Yingbin Zhang; Xiao Cheng; Qiangshan Yu (Geotechnical and Geological Engineering, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Efficient preparation and structural characterization of theabrownins from fermented summer green tea with Aspergillus cristatus (MK346334) in submerged fermentation - Jingqian Zheng; Jiayue Fang; Hongjun Liu; Zhiyong Xie; Xia Fan; Guijie Chen; Xiaoxiong Zeng (Food Chemistry, 2025)

Biotransformation and toxicity attenuation of 2,6-Dichlorobenzoquinone in simulated human gastrointestinal conditions: Insights from a systematic in vitro study - Lili Zheng; Guolong Chen; Kuangtao Fu; Zhen Wang; Xinyue Yuan; Hongjie Sun; Wenjing Deng; Zeqiong Xu; Hongjun Lin; Huachang Hong (Journal of Hazardous Materials, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Rice-fish coculture without phosphorus addition improves phosphorus availability in paddy soil by regulating phosphorus fraction partitioning and alkaline phosphomonoesterase-encoding bacterial community - Xing LIU; Yuting CHEN; Hongjun ZHENG; Daolin SUN; Jiaen ZHANG; Qi JIA; Qi CHEN (Pedosphere, 2025)

Reversing inhibition to promotion in phenol-ammonium metabolism via algal-microbial fuel cell: Mechanisms of phenol-ammonium interaction and synergistic removal - Yaqi Liu; Mengqi Zheng; Longyi Lv; Guowei Chen; Chengye Wang; Zhenhu Hu; Jingwei Feng; Binghan Xie; Hongjun Han; Wei Wang (Journal of Hazardous Materials, 2025)

Study on climate suitability for maize and technical implementation strategies under conservation tillage in Northeast China - Hongjun Liu; Wei Wan; Mandi Zheng; Jianwei Li; Shiwen Liu; Wei Lv; Yongxin Zhou; Zhong Liu (Soil and Tillage Research, 2025)

Enhancing ozone catalytic decomposition through acid treatment of α-MnO2 for improved activity and humidity resistance - Shangchao Xiong; Kai Zhang; Zhenghao Xu; Hongjun Ou; Yuanyuan Zheng; Xi Li; Yue Peng; Xubiao Luo; Junhua Li (Journal of Environmental Sciences, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

Enhanced removal of quinoline and nitrate in synthetic photovoltaic wastewater by non-aerating algae-bacteria symbiosis system: Microbial environmental response and nitrogen metabolism - Zipeng Yan; Mengqi Zheng; Yan Wang; Hao Shen; Yaqi Liu; Jie Wang; Hong Mei; Yuying Du; Yantao Zhou; Kuizu Su; Hongjun Han (Journal of Water Process Engineering, 2024)

Stimuli-responsive sulfur-containing amino acid functionalized boron nitride nanosheets as nanocarriers via improved adhesion to enhance antibacterial performance against plant diseases - Li Hao; Ziting Yin; Mei Guan; Qiangcheng Zheng; Zitao Feng; Jialin Zeng; Jinhui Wang; Huayao Chen; Jinhao Zhao; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2024)

Rice-fish coculture without phosphorus addition improves paddy soil nitrogen availability by shaping ammonia-oxidizing archaea and bacteria in subtropical regions of South China - Xing Liu; Daolin Sun; Huaqiao Huang; Jiaen Zhang; Hongjun Zheng; Qi Jia; Min Zhao (Science of The Total Environment, 2024)

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Experimental and numerical investigation on the impact of MS2AF on local scour protection performance - Chenghao Zhu; Qiheng Li; Jianguo Zheng; Hongjun Liu; Peng Yu (Ocean Engineering, 2024)

Dynamical graph neural network with attention mechanism for epilepsy detection using single channel EEG - Yang Li; Yang Yang; Qinghe Zheng; Yunxia Liu; Hongjun Wang; Shangling Song; Penghui Zhao (Medical & Biological Engineering & Computing, 2024)

Insights into synergistic metabolism of phenol and ammonium pollutants in treating coal gasification wastewater by algal-microbial fuel cell - Chengye Wang; Mengqi Zheng; Guowei Chen; Zipeng Yan; Binghan Xie; Wei Wang; Hongjun Han (Journal of Water Process Engineering, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Extracellular vesicles from human umbilical cord mesenchymal stem cells prevent steroid-induced avascular necrosis of the femoral head via the PI3K/AKT pathway - Puji Peng; XueZhong Wang; Chen Qiu; Wendi Zheng; Hongjun Zhang (Food and Chemical Toxicology, 2023)

Micropore sites in ferrihydrite are responsible for its higher affinity towards As(III) relative to As(V) - Qian Zheng; Shuxin Tu; Yiwen Chen; Hongjun Zhang; William Hartley; Bangjiao Ye; Lu Ren; Juan Xiong; Wenfeng Tan; Andreas Kappler; Jingtao Hou (Geochimica et Cosmochimica Acta, 2023)

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

Multiple-Stage Mineralization in the Huayangchuan U−REE−Mo−Cu−Fe Ore Belt of the Qinling Orogen, Central China: Geological and Re−Os Geochronological Constraints - Hongjun Jiang; Chunsi Yang; Dequan Wang; Hui Zheng; Jie Li; Huayong Chen (Journal of Earth Science, 2022)
The Huayangchuan ore belt is located in the western segment of Xiaoqinling Orogen in the southern margin of the North China Craton (NCC), and hosts voluminous magmatism and significant U−REE−Mo−Cu−Fe polymetallic mineralization. However, geochronological framework of the various mineralization phases in this region is poorly understood. Here, we present new Re−Os isochron ages on magnetite from the Caotan Fe deposit (2 675 ± 410 Ma, MSWD = 0.55), and on pyrite from the Jialu REE deposit (2 127 ± 280 Ma, MSWD = 1.9) and Yuejiawa Cu deposit (418 ± 23 Ma, MSWD = 11.5), and Re−Os weighted average model age on pyrite from the Taoyuan Mo−U deposit (235 ± 14 Ma, MSWD = 0.17). These ages, combined with regional geology and mineralization ages from other deposits, suggest that mineralization in the Huayangchuan ore belt lasted from the Neoarchean to the Late Mesozoic. The mineralization corresponds to regional tectono-magmatic events, including the Neoar-chean alkali magmatism (REE mineralization), Paleoproterozoic plagioclase-amphibolite emplacement (Fe mineralization), Paleoproterozoic pegmatite magmatism (U mineralization), Paleozoic Shangdan oceanic slab subduction-related arc magmatism (Cu mineralization), Early Mesozoic Paleo-Tethys Ocean subduction-related arc magmatism (Mo−U mineralization), and Late Mesozoic Paleo-Pacific oceanic plate subduction direction change-related Mo(-Pb) mineralization. We proposed that the Huayang-chuan ore belt has undergone prolonged metallogenic evolution, and the magmatism and associated mineralization were controlled by regional geodynamic events.

Enhanced nitrogen removal of coal pyrolysis wastewater with low COD to nitrogen ratio by partial nitrification-denitrification bioprocess assisted with polycaprolactone - Zhengwen Zhang; Chunyan Xu; Dan Zhong; Yuxing Han; Hongjun Han; Mengqi Zheng; Hao Zhu (Environmental Science and Pollution Research, 2019)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Chromosomally located gene fusions constructed in Acinetobacter sp. ADP1 for the detection of salicylate - Wei E. Huang; Hui Wang; Hongjun Zheng; Linfeng Huang; Andrew C. Singer; Ian Thompson; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary Acinetobacter sp. ADP1 is a common soil‐associated bacterium with high natural competency, allowing it to efficiently integrate foreign DNA fragments into its chromosome. This property was exploited to engineer salicylate‐inducible luxCDABE and green fluorescent protein (GFP) variants of Acinetobacter sp. ADP1. Specifically, Acinetobacter sp. ADPWH _lux displayed the higher sensitivity when comparing the two variants (minimum detection c . 0.5–1 µM salicylate) and a faster turnover of the lux marker gene, making it suitable for whole‐cell luminescence assays of salicylate concentration. In contrast, the longer maturation and turnover times of the GFP protein make the Acinetobacter sp. ADPWH _gfp variant more suited to applications involving whole‐cell imaging of the presence of salicylate. The sensitivity of the luxCDABE variant was demonstrated by assaying salicylate production in naphthalene‐degrading cultures. Assays using ADPWH _lux specifically mapped the kinetics of salicylate production from naphthalene and were similar to that observed by high‐performance liquid chromatography (HPLC) data. However, ADPWH _lux exhibited the higher sensitivity, when compared with HPLC, for detecting salicylate production during the first 24 h of naphthalene metabolism. These data demonstrate that the engineered Acinetobacter variants have significant potential for salicylate detection strategies in laboratory and field studies, especially in scenarios where genetic stability of the construct is required for in situ monitoring.